AQUIFER VULNERABILITY EVALUATION IN SOUTHWESTERN NIGERIA FROM AHP-GODT MODEL USING GEO-ELECTRICAL DERIVED PARAMETERS - Saminu Olatunji; Ahmed Muyiwa Emiola; Adewale Warith Adebisi (Jurnal Meteorologi dan Geofisika, 2021)
The study aimed  to determine the exposure levels of the subsurface aquiferous layers, owing to the alarming rate of contamination of the groundwater within 8.150 0N - 8.156 0N and 4.244 0E - 4.248 0E. Thus, aquifers' overlying layers, resistivity, and thickness anomalies were determined to generate an aquifer vulnerability map. A multi-criteria decision method of estimated Groundwater confinement, Overlying strata, Depth to Aquifer, and Topography index approach was implemented. Schlumberger's Vertical Electrical Sounding technique was implemented to acquire 30 Vertical Electrical Sounding points under a maximum half-current electrode separation (AB/2) of 65 m. IP2Win geophysical software packages were used to analyze the varying layer resistivity, depth, thickness, and also the sounding curves of the study area. The 2D model revealed a maximum of four geo-electric layers. The layers' resistivity and thickness ranges are clayey silt topsoil (52.5-1104 Ωm; 0.5-9.59 m), weathered layer (10.3-804 Ωm; 0.6-12.1 m), fractured basement (5.5-50832 Ωm; 6.7-18.1 m) and fresh basement (8.3-27348 Ωm; infinity m). On the Groundwater Overlying Strata Depth to Aquifer and Topography model scale, the area is generally characterized by the moderate vulnerability. Implying here is that aquifers have a moderate protective capacity in which the overlying strata above the aquifer are mostly impermeable layers (clay and silt) of high thickness and low porosity.